ROBSON’S TEN GROUP CLASSIFICATION SYSTEM FOR DECREASING CESAREAN SECTION RATES IN 2ND MATERNITY HOSPITAL IN SAMARKAND - Abduganieva Hilola Abduhafiz kizi; Agababyan L.R (Scientific Impulse, 2023)
This article discusses Robson's ten-group classification system for reducing cesarean rates and its use in the Samarkand maternity hospital.